Development of a Mobile App for Inverter System Management - Arowolo, Matthew Oluwole; Oyetade, Emmanuel Akinyemi; Agboola, Oluwaseun Samuel; George, Oluwatosin Steven (ABUAD Journal of Engineering Research and Development (AJERD), 2023)
In many developing nations, inconsistent power supply has led to a reliance on generators for residential energy needs, resulting in increased noise and air pollution. In response, the adoption of inverters has gained prominence as a cleaner and safer alternative. However, the lack of remote monitoring and control capabilities has limited the widespread application of traditional inverters. While previous research efforts have focused on mobile app development for inverter systems, the observed limitations in accuracy, precision, and response time have prompted the need for further advancements. This study addresses these challenges through the development of a mobile app for precise inverter system control and monitoring, leveraging the Blynk app's remote-control features. The user-friendly interface of the application enhances accessibility and usability. A specialized control device, integrated with the inverter system, utilizes the ESP32 microcontroller for efficient and low-power operation. Performance evaluation of the developed system yielded an impressive 94.15% accuracy and an optimal precision of 0.98%. The recorded average response time of 1.2 seconds highlights the system's efficient and prompt responsiveness. These findings demonstrate the suitability of the developed mobile application for robust monitoring and control of inverter systems. Furthermore, the identified scope for improvement includes enhancing the response time using 5G networks and ensuring the system's compatibility with evolving technological standards.